Complement Factor C5a Inhibits Apoptosis of Neutrophils-A Mechanism in Polytrauma? - Ehrnthaller, Christian; Braumueller, Sonja; Kellermann, Stephanie; Gebhard, Florian; Perl, Mario; Huber-Lang, Markus (Journal of Clinical Medicine, 2021)
Life-threatening polytrauma results in early activation of the complement and apoptotic system, as well as leukocytes, ultimately leading to the clearance of damaged cells. However, little is known about interactions between the complement and apoptotic systems in PMN (polymorphonuclear neutrophils) after multiple injuries. PMN from polytrauma patients and healthy volunteers were obtained and assessed for apoptotic events along the post-traumatic time course. In vitro studies simulated complement activation by the exposure of PMN to C3a or C5a and addressed both the intrinsic and extrinsic apoptotic pathway. Specific blockade of the C5a-receptor 1 (C5aR1) on PMN was evaluated for efficacy to reverse complement-driven alterations. PMN from polytrauma patients exhibited significantly reduced apoptotic rates up to 10 days post trauma compared to healthy controls. Polytrauma-induced resistance was associated with significantly reduced Fas-ligand (FasL) and Fas-receptor (FasR) on PMN and in contrast, significantly enhanced FasL and FasR in serum. Simulation of systemic complement activation revealed for C5a, but not for C3a, a dose-dependent abrogation of PMN apoptosis in both intrinsic and extrinsic pathways. Furthermore, specific blockade of the C5aR1 reversed C5a-induced PMN resistance to apoptosis. The data suggest an important regulatory and putative mechanistic and therapeutic role of the C5a/C5aR1 interaction on PMN apoptosis after polytrauma.
CRIS-Team WoS Importer:2021-08-06